Industry-wide competitiveness assessment through fuzzy synthetic evaluation: the case of cement industry - Ulubeyli, Serdar (Journal of Business Economics and Management, 2017)
This study aims to develop a fuzzy force assessment model (FFAM) for quantifying industry-wide competition conditions (ccs) using five-force framework. It employed fuzzy synthetic evaluation to assess ccs of forces and industry, and real case of Turkish cement industry was demonstrated. As a result, FFAM provides a comprehensive and practical device. As empirical findings, ccs in cement industry are medium-to-high, and pressure from substitutes is the most effective force, followed by intensity of competitors’ rivalry, bargaining power of buyers, bargaining power of suppliers, and threat of entrants. Consequently, this study is first to propose a structured and fuzzy five-force quantification model and to assess ccs in cement industry.